La science et la victime statistique - Sheila Jasanoff (Revue d'anthropologie des connaissances)
The advent of mass torts in US federal courts in the latter third of the 20th century accelerated a process of modernization in an institution that was unprepared for standardized approaches to dispute resolution. Faced with large-scale technological disasters, in particular, courts struggled to reform both their procedures and their fact-finding approaches in order to deal with multiple claimants in consolidated proceedings. Using silicone gel breast implant litigation as a case study, this paper argues that the attempt to marry judicial concerns for individual justice with administrative concerns for speed, efficiency and economy has produced anomalous results. The testimony of the clinician and the victim has become less relevant as judicial remedies take account of injuries done to classes of plaintiffs. Subjective claims about the body are subordinated to statistical correlations between exposure and grouped complaints. At the same time, the transfer of fact-finding authority from juries to judges under new evidentiary rules has privileged the judiciary’s lay knowledge and experience over that of the jury. While these transformations may hasten the processing of cases, the paper questions whether the courts can legitimately take on board the issues of risk and social justice in contemporary industrial societies.